POLIMORFISMO DE CYP2C9: ESTUDO DA RELAÇÃO DO USO DE AGROTOXICOS COM O DESENVOLVIMENTO DE DOENÇAS EM AGRICULTORES DO ESPÍRITO SANTO - Kohls, Victor Nogueira da Gama (2020)
Brazil is the leader of the world ranking in consumption of pesticides. The indiscriminate use of pesticides associated with the lack of technical information on the use of the same and of personal protective equipment (PPE), can put the health of both th